39.3k views
3 votes
When factored completely, which is a factor of 3x3 − 9x2 − 12x A. L(x − 3) B. (x − 4) C. (3x − 1) D. <(3x − 4)

User Firzen
by
5.3k points

1 Answer

4 votes

Solution:


3x^3-9x^2-12x

Step 1:

Factor out the common term

The common term is 3x

By doing this, we will have


\begin{gathered} 3x^3-9x^2-12x=3x((3x^3)/(3x)-(9x^2)/(3x)-(12x)/(3x)) \\ =3x(x^2-3x-4) \end{gathered}

Step 2:

Factorise the quadratic expression in the bracket


3x(x^2-3x-4)

By doing this, we will have to look for two factors to multiply to give i4 and if we add them together, we will have -3

The two factors are -4 and +1

therefore,

Replace -3x with -4x + x


\begin{gathered} 3x(x^2-3x-4) \\ =3x(x^2-4x_{}+x-4) \\ =3x(x(x-4)+1(x-4) \\ =3x(x+1)(x-4) \end{gathered}

Hence,

The final answer is = (x-4)

User Quadwwchs
by
4.8k points